THE SOCIAL COST OF BETRAYAL: HOW BROKEN TRUST AFFECTS RELATIONSHIPS AND WELLBEING (Contemporary Journal of Social Science Review, 2025)
It is a severe violation of inter-relationships that jeopardizes trust, interferes with emotional safety, and has a detrimental effect on wellbeing. The current research involved the correlation of the experiences of betrayal and various measures of psychological and social wellbeing. A quantitative cross-sectional survey including a sample of 300 participants who were requested to fill in standardized measures on betrayal, depression, anxiety, stress, self-esteem, social connectedness, and life satisfaction was carried out. Multiple linear Regression analyses revealed that betrayal was a significant predictor of greater psychological distress and a smaller positive wellbeing. Particularly, those whose betrayal experiences were higher had higher levels of depressive symptoms, anxiety and stress and lower levels of self-esteem, social connectedness and life satisfaction. One-way ANOVA also indicated that respondents in high betrayal reported much worse results in all the measures of wellbeing than those of low and moderate betrayal. Such results indicate that betrayal can be costly psychologically and socially as a relational trauma with the extensive implication of mental well-being and interpersonal performance. The research notes that therapeutic interventions to build trust and develop resilience and preventive interventions that focus on relationships by emphasizing transparency, communication, and accountability should be done.